Randomized Controlled Trial of Tranexamic Acid’s Effect on Bleeding Length: A Study on DMPA Users with Abnormal Uterine Bleeding Who Receive Low-Dose Oral Contraceptive Pill - Rabiah Adawiyah; Inu Mulyantoro; Julian Dewantiningrum; Noor Pramono (Faculty of Medicine, Diponegoro University, 2020)
ABSTRACTBackground: Contraceptive injection is the most common contraception used in Indonesia. Among the contraceptive injections, depomedroxy progesterone acetate (DMPA) is the most effective method with pregnancy rate of 0,3 pregnancy in 100 women annually. Abnormal uterine bleeding (AUB) is a common side effect occurred in DMPA users which leads to the discontinuation of contraception.Objective: To explore the effect of tranexamic acid on bleeding length for DMPA users with AUB who receive low dose Oral Contraceptive Pills (OCP).Methods: We performed double blind randomized control trial between two groups to investigate the effect of tranexamic in managing AUB in DMPA users who receive low dose OCP. This study was performed in Dr. Kariadi Hospital Semarang, Indonesia. Forty-four subjects were divided into two groups, equally. Group 1 received 250 mg tranexamic acid four times a day for 5 days and OCP once a day for 28 days, while Group 2 received placebo four times a day for 5 days and OCP once a day for 28 days. Both groups were evaluated for bleeding length during treatment and were analyzed using Mann Whitney for post treatment with tranexamic acid.Results: The mean bleeding length was 5.2±3.62 days and 9.2±6.16 days in group 1 and 2 respectively. These bleeding lengths were significantly different between both groups (p=0.018). The precentage of subjects in whom bleeding was stopped during the first week after initial treatment was significantly higher in group 1 than group 2 (77,3 % vs 45,5 %, p<0,030).Conclusion: Tranexamic acid significantly reduced the bleeding length in DMPA users who use OCP.